Comprehensive fecal metabolomics and gut microbiota study of the protective mechanism of herbal pair Polygonum hydropiper-Coptis chinensis in rats with stress-induced gastric mucosal damage - Ren, Shouzhong; Ren, Chenhui; Zhao, Yamei; Niu, Haiyan; Xie, Yiqiang (Frontiers in Pharmacology, 2024)
Stress-related gastric mucosal lesions (SGMLs) are the most common complication in critical care patients. Previous studies have demonstrated that herbal pair (HP), Polygonum hydropiper-Coptis chinensis (HP P-C) has the anti-SGML effect. However, the underlying mechanism of HP P-C against SGML remains elusive. This study aimed to elucidate how HP P-C extracts exert their protective effects on SGML by examining the role of gut microbiota and metabolites. SD rats were pretreated with different doses of HP P-C extracts for six days, followed by inducing SGML with Restraint water-immersion restraint stress (RWIRS). After a comprehensive evaluation of serum and gastric tissue indicators in rats, 16S rRNA sequencing and metabolomics analyses were conducted to assess the impact of HP P-C on the fecal microorganisms and metabolites and their correlation. Animal experiment suggested that pretreatment with HP P-C effectively reduced the gastric mucosal lesions, remarkably increased superoxide dismutase (SOD) activity in SGML model rats induced by RWISWIRS. 16S rRNA sequencing analysis showed that HP P-C altered the composition of gut microbiota by raising the abundance of Lactobacillus and Akkermansia. In addition, metabolomics data identified seventeen main differential metabolites related to RWISWIRS-induced gastric mucosal injury, primarily involving in tyrosine metabolism and betalain biosynthesis. HP P-C was found to regulate tyrosine metabolism and betalain biosynthesis by down-regulating the tyramine, L-tyrosine and L-dopa and up -regulating the gentisic acid and dopaquinone. Taken together, this study indicated that HP P-C could effectively protect against RWISWIRS-induced gastric mucosal lesions by modulating intestinal flora and metabolites.